1991
DOI: 10.1103/physrevlett.66.1942
|View full text |Cite
|
Sign up to set email alerts
|

Mixing effects in theA+B→0 reaction-diffusion scheme

Abstract: We study analytically the irreversible reaction A +B-• 0 under laminar stirring, for equal overall particle concentrations. In contrast to the usually found algebraic decays, here the reactant concentrations display exponential patterns, which stem from the mixing kinetics. The crossover from this short-time behavior to the classical kinetic law in a fully mixed system is also investigated. Furthermore, disorder effects are fundamental, since for strictly regular patterns the short-time decay shows an exponent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…The utility of the lamellar model was demonstrated by Clifford et al [13], who found reasonable agreement with results from two-dimensional simulations of the full advection-reactiondiffusion problem [6], although, as we have already remarked, at large Péclet number the latter simulations are known to be inaccurate [27]. Of particular note are the works of Sokolov and Blumen [41,42], who analysed a single reaction taking place in a lamellar structure, with special emphasis on 'fast' reactions, for which a great deal of analytical progress is possible, and of Muzzio and Ottino [19,20], who examined the evolution of a lamellar structure in which only the primary reaction takes place (i.e., the case k 2 = 0), at infinite rate. The latter focused on the evolution of the distribution of striation thicknesses, which is not our direct concern here, and commented that it would be interesting to include fluid mechanical mixing effects into their lamellar model.…”
Section: Lamellar Modelssupporting
confidence: 74%
See 2 more Smart Citations
“…The utility of the lamellar model was demonstrated by Clifford et al [13], who found reasonable agreement with results from two-dimensional simulations of the full advection-reactiondiffusion problem [6], although, as we have already remarked, at large Péclet number the latter simulations are known to be inaccurate [27]. Of particular note are the works of Sokolov and Blumen [41,42], who analysed a single reaction taking place in a lamellar structure, with special emphasis on 'fast' reactions, for which a great deal of analytical progress is possible, and of Muzzio and Ottino [19,20], who examined the evolution of a lamellar structure in which only the primary reaction takes place (i.e., the case k 2 = 0), at infinite rate. The latter focused on the evolution of the distribution of striation thicknesses, which is not our direct concern here, and commented that it would be interesting to include fluid mechanical mixing effects into their lamellar model.…”
Section: Lamellar Modelssupporting
confidence: 74%
“…The chemical species diffuse (in the x-direction) and react; they are also advected by a straining flow (u, v) = (−µx, µy), which allows us to retain the effect of mixing in stretching the interface exponentially in time, but without the corresponding folding [2,12,13,[16][17][18][40][41][42]. The appropriate dimensionless governing equations are then…”
Section: Single Planar Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] This regime is due to the spontaneous separation of reactants and makes the AϩB→0 scheme a very interesting model, e.g., for the investigations of effects of mixing procedures applied to diffusion-controlled reactions which are otherwise slow and ineffective. 5,6 The reaction schemes considered in such a context are normally oversimplified because no particles interactions ͑except those leading to the reaction͒ are considered. However, in many situations such interactions can be of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…The classical form is obeyed when the concentrations are homogeneous at all times, which can be achieved through efficient procedures such as mixing by dilatational flow [11], tossing [12], or unbounded shear flow [13][14][15]. In general realistic mixing flows, especially in two dimensions, are less effective [1].…”
mentioning
confidence: 99%